MAKNA SIMBOLIK RITUAL ADAT WEWAR HULER WAIR (RECIKAN AIR AWAR-AWAR) BAGI MASYARAKAT ADAT DESA POGON KABUPATEN SIKKA - Kristina Wanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The indigenous community of Pogon Village is strongly bound to three elements of power that form an integrated belief system and represent ancestral heritage preserved to this day. These three elements of belief are God, Nature, and Spirits/Ancestors. The implementation of these beliefs can be found in the traditional ritual Wewar Huler Wair (the sprinkling of awar-awar water). This study explores in depth the symbolic meaning contained in the Wewar Huler Wair ritual. The purpose of this research is to describe the symbolic meanings embedded in the ritual and to explain the underlying intentions for performing the Wewar Huler Wair (sprinkling of awar-awar water) traditional ceremony. The method used is qualitative, with data collected through interviews and field observations. The findings of this study indicate that the Wewar Huler Wair ritual serves as a symbolic expression of gratitude addressed to the three elements of power, believed by the local community. This ritual is regarded as sacred and is typically performed during moments of joy and celebration, adjusted to the category of customary events being held.